Evidence of benefit of lower limb exercise immediately after major abdominopelvic surgery - Kar, Manoranjan; Islam, M. Monirul; Maiti, Ayan (International Journal of Research in Medical Sciences, 2025)
Background: Repeated active dorsiflexion of the ankle joint in knee and hip flexion state (moving the whole lower limb) i.e. active lower limb exercise (ALLE). Benefits of ALLE over non-ALLE approaches during the postoperative period in patients following major abdominopelvic surgery was studied. The aims of the study were to determine whether early return of intestinal peristaltic sound (IPS), early pain relief, early control of blood sugar in diabetic patients and early return of wellbeing of patients occurred in patients undergoing major abdominopelvic surgery. Methods: Randomized comparative study was done. 100 patients above 15 years of age who underwent major abdominopelvic surgery participated in this study from one of the government medical colleges. Samples were randomly allocated to the experimental and control group. Experimental group were counselled, motivated, and trained in pre-operative period, to do ALLE in short interval after operation. Data was collected on post operative day (POD) 0, POD 1, POD 2, and POD 3. The tools used to collect data was visual analogue scale (VAS) for pain, capillary blood glucose (CBG) for blood sugar level, IPS for intestinal motility and WHO-5 well-being index for assessment of wellbeing. Results: Patients who were in the test group showed- better pain relief and lees use of analgesic (p value=0.0259), better control of blood sugar in diabetic patients (p value=0.0076), early return of IPS (p value=0.0002) and early return of wellbeing (p value=0.0056). Conclusions: ALLE after major abdominopelvic surgery is very effective practice for better relief of pain, early return of IPS, better control of blood sugar in diabetic patients and less anxiety and more comfort.